2021
DOI: 10.56093/ijas.v91i7.115120
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient and residue management in zero tilled-direct seeded basmati rice (Oryza sativa)-wheat (Triticum aestivum) system

Abstract: To assess the effect of nutrient and residue management on the performance of zero till - direct seed rice (DSR) (Oryza sativa L.)-wheat (Triticum aestivum L.) cropping system in partially reclaimed sodic soils, a three-year field experiment was conducted at ICAR-CSSRI during kharif and rabi 2016-18. The experiment was conducted in factorial randomized block design with 8 nutrient management options as first factor and two levels of residue management as second factor with three replications. Plant height, num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…The highest dry weight was recorded in the maturity stage due to the mass accumulation of the crop and also the dry weight increased with application of plant growth regulator, might be due to the better growth of healthy seedlings. Similar findings were also reported by Kumar and Yadav [7].…”
Section: Influence Of Plant Growth Regulator (Ta-41) On Dry Weight Of...supporting
confidence: 92%
“…The highest dry weight was recorded in the maturity stage due to the mass accumulation of the crop and also the dry weight increased with application of plant growth regulator, might be due to the better growth of healthy seedlings. Similar findings were also reported by Kumar and Yadav [7].…”
Section: Influence Of Plant Growth Regulator (Ta-41) On Dry Weight Of...supporting
confidence: 92%
“…In order to save water and labor and promote conservation agriculture (CA), with no/reduced tillage, it is absolutely essential to replace puddle transplanting with direct seeding. In South Asia, DSR is being practiced on terraced and sloppy lands of Bangladesh, along the coast and Western Himalayan region of India (Gupta et al 2007). The author found that after two seasons of experimentation (2010-2012) at Rampur the rice yield under DSR was at par with PTR.…”
Section: Resultsmentioning
confidence: 99%
“…Kumar et al . [ 34 ] reported that the inclusion of a legume crop in the system increased the organic carbon and availability of N, P and K in the soil. Boone [ 35 ] reported that 16–33% of the total C assimilated by plants is released directly into the soil by roots, which contributes to 30–60% of the organic C pool in soil.…”
Section: Discussionmentioning
confidence: 99%